1996
DOI: 10.1073/pnas.93.22.12451
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for the interferon-inducible, double-stranded RNA-activated protein kinase PKR in the tumor necrosis factor-induced apoptosis in U937 cells.

Abstract: Tumor necrosis factor a (TNF-a) is wellcharacterized for its necrotic action against tumor cells; however, it has been increasingly associated with an apoptosis-inducing potential on target cells. While the signaling events and the actual cytolytic mechanism(s) for both TNFca-induced necrosis and apoptosis remain to be fully elucidated, we report here on (i) the ability of TNF-a to induce apoptosis in the promonocytic U937 cells, (ii) the discovery of a cross-talk between the TNF-ai and the interferon signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
114
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 21 publications
12
114
0
Order By: Relevance
“…Using this trans-dominant negative property of the catalytically inactive PKR, we have shown that a functional PKR pathway is required to induce apoptosis in response to serum deprivation or TNF␣ treatment. Our results confirm and extend recent observations that implicate PKR as a general transducer of the apoptotic response (6,32,33,35). Although it was appreciated for many years that dsRNA in the presence of interferon is toxic to cells, it was only recently suggested that PKR mediates the apoptotic response to dsRNA upon vaccinia virus (6,35,39) and influenza virus (40) infection.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Using this trans-dominant negative property of the catalytically inactive PKR, we have shown that a functional PKR pathway is required to induce apoptosis in response to serum deprivation or TNF␣ treatment. Our results confirm and extend recent observations that implicate PKR as a general transducer of the apoptotic response (6,32,33,35). Although it was appreciated for many years that dsRNA in the presence of interferon is toxic to cells, it was only recently suggested that PKR mediates the apoptotic response to dsRNA upon vaccinia virus (6,35,39) and influenza virus (40) infection.…”
Section: Discussionsupporting
confidence: 81%
“…It is most likely that poly(I)⅐poly(C) alone did not affect NIH3T3 cells due to their low levels of PKR. These results are in agreement with previous observations (32,33) and support the idea that dsRNA is toxic to NIH3T3 cells that have a functional PKR pathway.…”
Section: Eif-2␣ Phosphorylation Mediates Pkr-dependent Apoptosissupporting
confidence: 83%
See 2 more Smart Citations
“…Caspase Assay U937 cells (ATCC) sensitive to TNF-α-induced apoptosis 7 were cultured in RPMI 1640 medium containing 10% fetal bovine serum at 37 °C and 5% CO 2 /O 2 . Cells were grown in every other well of a 384-well NUNC sterile, clear plate (25,000 cells/well, 25 µL/well) for 18 h. Solutions of the carbohydrates at the indicated concentrations (0.01 -4000 µM in sterile PBS) were pre-incubated with TNF-α (1 µL/well of a 125 ng/mL solution in sterile PBS) at rt.…”
Section: S6mentioning
confidence: 99%